2020
DOI: 10.1073/pnas.2002792117
|View full text |Cite
|
Sign up to set email alerts
|

Long-range intramolecular allostery and regulation in the dynein-like AAA protein Mdn1

Abstract: Mdn1 is an essential mechanoenzyme that uses the energy from ATP hydrolysis to physically reshape and remodel, and thus mature, the 60S subunit of the ribosome. This massive (>500 kDa) protein has an N-terminal AAA (ATPase associated with diverse cellular activities) ring, which, like dynein, has six ATPase sites. The AAA ring is followed by large (>2,000 aa) linking domains that include an ∼500-aa disordered (D/E-rich) region, and a C-terminal substrate-binding MIDAS domain. Recent models suggest that i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 57 publications
(104 reference statements)
0
13
0
Order By: Relevance
“…Consistent with this idea, Brownian dynamics simulations have shown that docking of the MIDAS domain onto the AAA ring stretches the unstructured portion of the linker such that 1-2 pN of tension is generated (Mickolajczyk et al, 2020). This tension would be transmitted along the MIDAS-UBL bond axis, and its magnitude may even be enhanced by ATP-dependent motions propagated from the AAA ring (Chen et al, 2018;Ulbrich et al, 2009).…”
Section: Introductionmentioning
confidence: 84%
See 3 more Smart Citations
“…Consistent with this idea, Brownian dynamics simulations have shown that docking of the MIDAS domain onto the AAA ring stretches the unstructured portion of the linker such that 1-2 pN of tension is generated (Mickolajczyk et al, 2020). This tension would be transmitted along the MIDAS-UBL bond axis, and its magnitude may even be enhanced by ATP-dependent motions propagated from the AAA ring (Chen et al, 2018;Ulbrich et al, 2009).…”
Section: Introductionmentioning
confidence: 84%
“…Mdn1 approaches the pre-60S particle and binds via its AAA ring, at which point the MIDAS domain both docks onto the AAA ring and binds the UBL-domain substrate (Chen et al, 2018;Kater et al, 2020;Sosnowski et al, 2018). In this MIDAS-docked state, Mdn1's unstructured linker is stretched, building 1-2 pN of tension that is propagated along the MIDAS-UBL bond axis (Mickolajczyk et al, 2020). While the directionality of Mdn1 force generation has not been determined, one possibility is that ATPase activity in the AAA ring adds more tension to the unstructured linker, which would be propagated to the MIDAS-UBL interaction (Figure 4G), and thereby activate the MIDAS-UBL catch bond.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although a UBL domain is structurally distant from extracellular integrin ligands, it is possible that Mdn1 may similarly use mechanoregulation for its function. Consistent with this idea, Brownian dynamics simulations have shown that docking of the MIDAS domain onto the AAA ring stretches the unstructured portion of the linker such that 1–2 pN of tension is generated ( Mickolajczyk et al, 2020 ). This tension would be transmitted along the MIDAS-UBL bond axis, and its magnitude may even be enhanced by ATP-dependent motions propagated from the AAA ring ( Chen et al, 2018 ; Ulbrich et al, 2009 ).…”
Section: Introductionmentioning
confidence: 90%